Optimization of Antibacterial Production and Molecular Identification of Endophytic Bacteria Isolated from Papaya (Carica papaya L.) Seeds - Esti Rizkiana Pratiwi; Nadiah Al Batati; Rizka Kusuma Ningrum (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2026)
Papaya seed endophytic bacteria have been reported to exhibit antibacterial activity against pathogenic microorganisms, including Staphylococcus aureus and Escherichia coli. However, their antibacterial production remains suboptimal. This study aimed to determine the optimal conditions for antibacterial production and to identify the most potent bacterial isolate through 16S rRNA gene-based molecular analysis. Three endophytic bacterial isolates (CPA2, CPA8, and CPA9) were evaluated. Characterization was performed based on pH variations (5, 7, and 9) and growth media (Nutrient Broth (NB) and Tryptic Soy Broth (TSB)), followed by antibiotic sensitivity testing against ciprofloxacin, amoxicillin, gentamicin, and tetracycline. Antibacterial activity was assessed using the Kirby–Bauer method against S. aureus and E. coli. The results showed that all isolates grew optimally in TSB medium at neutral pH (7). Ciprofloxacin and tetracycline exhibited stronger inhibitory effects compared to gentamicin and amoxicillin. Among the isolates, CPA2 in TSB media pH 7 demonstrated the highest antibacterial activity, producing inhibition zones of 30.2 ± 1.77 mm against S. aureus (very strong) and 11.8 ± 0.02 mm against E. coli (strong). Molecular identification revealed that isolate CPA2 was closely related to Bacillus cereus strain JCM 2152 with 99.90% similarity. In conclusion, papaya seed endophytic bacteria, particularly isolate CPA2, show significant potential as a source of antibacterial compounds under optimized culture conditions. These results have the potential as an alternative source of antibacterial agents